The societal and economic impact of reforestation strategies and policies in Southeast Asia—a review - Ahmadzai, Mujib Rahman; Zaki, Pakhriazad Hassan; Ismail, Mohd Hasmadi; Bawon, Paiman; Karam Singh, Daljit Singh (Multidisciplinary Digital Publishing Institute, 2022)
This paper assesses the existing reforestation and forest conservation policies and strategies in Southeast Asia and how they have impacted people’s lives. Southeast Asia contains 11 countries and is home to 20% of the world’s species. Unfortunately, the region has been practising deforestation at an alarming rate. The main cause of deforestation in the region is the creation of land for agriculture, with forest fires and the growing demand for timber also contributing. As a result, the region has lost 376,000 km2 of forest in the last 30 years. Parts of the region have been involved in international efforts to protect forests, such as the 2016 Paris Agreement. However, some of these policies have not made much difference because most countries are not willing to support the necessary strategies. From the study findings, the main strength of the existing polices and strategies is that they are being amended to suit different changes in demographics and the practical needs of the sector. The sector has been able to shift from the initial state forestry management to making forests a multi-sectoral economic development agent. On the other hand, there are few polices at the national level that ensure every citizen participates in tree planting and that they understand the need to stop deforestation. In addition, many countries in the region are less willing to join the international communities in fighting climate change; that is, they do not agree with international partnerships like the Pris Climate Change Agreement.